Sirolimus in the Management of Blue Rubber Bleb Nevus Syndrome: A Case Report and Review of the Literature - Bayan Musaed AlNooh; Nada Ghazi AlQadri; Muhtadi Alghubayn; Saad Mohammed AlAjlan (Karger Publishers, 2021)
Blue rubber bleb nevus syndrome (BRBNS) is a rare multifocal venous malformation (VM) that may affect any tissue or organ but mainly affects the skin, subcutaneous tissue and gastrointestinal (GI) tract. Patients present with serious anemia, treated with lifelong iron supplements and frequent blood transfusion secondary to chronic GI bleeding. Variable therapeutic modalities were used in the management of BRBNS; sirolimus (SRL), a mammalian target of rapamycin (mTOR) inhibitor, is found to be a promising therapy for vascular anomalies.